Antioxidant and Anti-Inflammatory Activities of Cutlassfish Head Peptone in RAW 264.7 Macrophages - Su-Jin Lee; Jeonghyeon Im; Svini Dileepa Marasinghe; Eunyoung Jo; Minthari Sakethanika Bandara; Youngdeuk Lee; Jaewon Lee; Gun-Hoo Park; Chulhong Oh (Antioxidants)
The rapid growth of the fisheries industry has resulted in numerous by-products, usually called waste, causing environmental and economic challenges. Recent advances in valorization techniques have highlighted the potential of these by-products as sources of bioactive compounds. This study aimed to investigate the antioxidant and anti-inflammatory activities of cutlassfish (Trichiurus lepturus) head peptone (CP) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. CP exhibited significant antioxidant activity, reducing ABTS and DPPH radical scavenging activity by up to 79.66% and 64.69%, respectively, with a maximum ferric-reducing antioxidant power (FRAP) value of 224.54 μM. CP enhanced macrophage proliferation (33.3%) and significantly mitigated LPS-induced oxidative and inflammatory responses, reducing nitric oxide (NO) production (60%) and reactive oxygen species levels (49.14%). CP suppressed the expression of inflammatory mediators, including inducible nitric oxide synthase (iNOS) and cyclooxygen-ase-2, and selectively inhibited the pro-inflammatory cytokines interleukin (IL)-1β and IL-6. Western blot analysis revealed that CP inhibited the phosphorylation of mitogen-activated protein kinases, including ERK, JNK, and p38, highlighting its role in modulating upstream inflammatory signaling pathways. CP exhibited significant antioxidant effects, particularly in scavenging ABTS and DPPH radicals, as well as reducing oxidative stress markers and inflammatory responses in LPS-stimulated macrophages. These findings suggest its potential not only as a therapeutic agent for conditions related to chronic inflammation, such as cardiovascular diseases and arthritis, but also as a functional ingredient in foods and nutraceuticals aimed at alleviating inflammation-related disorders.